Calendar of Events. (Communications of the ACM, 2015)
A calendar of computing systems events for 2015 is presented. Events include the Eighth ACM International Conference on Web Search and Data Mining on February 2 through 6 in Shanghai, China, the 20th ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming on February 7 through 11 in Burlingame, California, and the Fifth ACM Conference on Data and Application Security and Privacy on March 2 through 4 in San Antonio, Texas.